Ultra-durable, multi-template molecularly imprinted polymers for ultrasensitive monitoring and multicomponent quantification of trace sulfa antibiotics. Issue 14 (24th March 2021) - Liu, Yuanchen; Liu, Yujian; Liu, Zhiming; Hill, Jonathan P.; Alowasheeir, Azhar; Xu, Zhigang; Xu, Xingtao; Yamauchi, Yusuke
Abstract : Molecularly-imprinted polymers have been used for the selective and ultrasensitive monitoring of trace sulfa antibiotics avoiding sample matrix interference effects and leading to improved reusability of the relevant materials. Abstract : Traditional analysis methods are susceptible to interference caused by the complexity of sample matrices, and detector surface fouling arising from nonspecific adsorption of microorganisms (in biological samples) which leads in particular to a gradual loss of sensitivity. Imprinted materials can be used to effectively reduce interference originating in the matrices. However, the poor reproducibility and multicomponent quantification of trace antibiotics represent significant challenges to the detection process. Meanwhile, the high biological risk presented by bacterial antibiotic immunity and the persistence of antibiotics in foodstuffs, especially meat, both caused by the overuse of sulfonamide antibiotics, remain urgent issues. Here, we present the first example of a method for the accurate quantification of trace sulfa antibiotics (SAs) based on multi-template imprinted polymers (MMIPs). Levels of multiple SAs have been simultaneously successfully quantified by applying MMIP extraction coupled with UPLC-MS/MS analysis. This method shows excellent linearity of detection in the range of 0.1–500 μg L −1, and ultrasensitivity with low limits of detection of 0.03 μg L −1 . The maximum SA residue recovered from sample tissues by using MMIPs was 5.48 μg g −1 . MMIP-coupled UPLC-MS/MS quantification of SAs is an accurate and repeatable method for the monitoring of SA accumulation in mouse tissue samples. It also provides an effective strategy for the tracking and quantification of drugs in other biological samples.